Appropriate use of antibiotics: an unmet need. (March 2019) - López Romo, Alicia; Quirós, Rodolfo
Increasing bacterial resistance combined with a steady decline in the discovery of new antibiotics has resulted in a global healthcare crisis. Overuse of antibiotics, for example, in the poultry and cattle industry, and misuse and improper prescription of antibiotics are leading causes of multidrug resistance (MDR). The increasing use of antibiotics, particularly in developing countries, is a big concern for antibiotic resistance and can cause other health threats such as increased risk of recurrent infections and increased risk of cardiovascular death with chronic use of macrolides. Carbapenems are the last line of defense in many cases of resistant infection, but trends show that resistance against these agents is also increasing. This narrative review is based on relevant literature according to the experience and expertise of the authors and presents an overview of the current knowledge on antibiotic resistance, the key driving factors, and possible strategies to tackle antibiotic resistance. Collectively, studies show that hospital-wide antibiotic stewardship programs are effective in decreasing the spread of antibacterial resistance. As resistance varies according to local patterns of use, it is essential to observe the epidemiology at both a regional and an institutional level. Furthermore, adaptation of clinical guidelines is necessary, particularly for inpatient care. Future guidelines should include a justification step for continued treatment of antibiotic treatments and criteria for selection of antibiotics at the start of treatment. Nonantibiotic prevention strategies can limit infections and should also be considered in treatment plans. Vaccines against MDR organisms have shown some efficacy in phase II trials in critical care patients. Nonimmunogenic and microbiologic treatment options such as fecal transplants may be particularly important for elderly and immune-compromised patients.